2013
DOI: 10.7748/nop2013.10.25.8.29.e466
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting residents’ sleep in care homes

Abstract: Aims To understand sleep as part of the 24 hour provision of resident care by viewing it in the wider social context within the care home, exploring both the subjective experience of residents and the perceptions of staff. Methods Qualitative research in four care homes for older people consisting of semi-structured interviews and ethnographic observations. Interviews were conducted with 38 residents and 39 staff, and were analysed using a grounded theory approach. Findings The findings have highlighted some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The LOCK sleep intervention. In Phase 1, the LOCK sleep intervention will initially use intervention materials (assistance for developing teams and implementing the intervention, checklists, role-play scenarios, and videos) developed from the pilot 6-site VA nursing home implementation [34]. Throughout this phase, we will make additional re nements based on our intervention team's experiences from their previous work.…”
Section: Staff Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The LOCK sleep intervention. In Phase 1, the LOCK sleep intervention will initially use intervention materials (assistance for developing teams and implementing the intervention, checklists, role-play scenarios, and videos) developed from the pilot 6-site VA nursing home implementation [34]. Throughout this phase, we will make additional re nements based on our intervention team's experiences from their previous work.…”
Section: Staff Samplementioning
confidence: 99%
“…But another 2018 review noted that sleep disturbance remains extremely common for nursing home residents (32). Even when nursing homes do recognize the need for systems-level changes and act to make those changes, their efforts are often translated into a one-size-ts-all approach to implementation, ultimately overlooking the complex interplay between individual residents' needs, staff availability, and environmental barriers (33)(34)(35). Because good sleep results from a complex interplay of resident, staff-generated, and environmental factors (33), sleep regimens for nursing home residents work best when individualized instead of applied generically.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, different studies have reported that more than 60% of older adults living in a nursing home had some sleep difficulties (Fetveit & Bjorvatn, 2002;Martin & Ancoli-Israel, 2008). There are some possible causes for sleep problems observed in nursing home residents in addition to agerelated changes in sleep architecture, such as nocturia, environment-related noise (Gentili, Weiner, Kuchibhatil, & Edinger, 1997), inactivity, longer amounts of time spent in bed, lack of bright light exposure, poor sleep hygiene (Alessi & Schnelle, 2000;Neikrug & Ancoli-Israel, 2010), physical disabilities, practices in care homes (Ellmers, Arber, Luff, Eyers, & Young, 2013), polypharmacy, social disengagement, depression, dementia, room temperature and room sharing (Ye & Richards, 2018). These possible reasons are likely to increase the severity of sleep problems in nursing home residents.…”
Section: Introductionmentioning
confidence: 99%
“…Like hospitals, care homes, both with and without nursing care, support their residents twenty-four hours a day, seven days a week. However, despite approximately 425,000 elderly people living in care homes in England (Laing and Buisson, 2014), most of what we know about these settings is based on research that focuses on life in the home during the daytime (Ellmers et al, 2013). In place of a body of knowledge, there are just a handful of studies which focus on care homes outside of these hours.…”
mentioning
confidence: 99%
“…In addition to the clinical data, there is also evidence that incidences of challenging behaviour amongst residents is temporal, with certain behaviours, such as picking at things, pacing and aggression, being more common during the evening than the daytime (Cohen-Mansfield et al, 1992). There is also a small body of work looking at care homes during the night time (Ellmers et al, 2013;Eyers et al, 2013Eyers et al, , 2014Kerr et al, 2008;Kerr and Wilkinson, 2011;Luff, Ellmers, et al, 2011;Wilkinson, 2011). , in particular, note that residents in care homes for older adults are often unable to control their night-time environment and are, therefore, at risk of poorer quality of life during these hours.…”
mentioning
confidence: 99%